Graphene Encapsulated Al Particles for Improvement of Thermal Conductivity in Composites - Hwang, Jinuk; Tak, Woo-Seong; Mun, So Youn; Nam, Sangyong; Moon, Sook Young; Kim, Woo Sik (MDPI, 2020)
Graphene reinforced aluminum matrix composites (GRAMCs) with improved thermal conductivity were prepared via a pH-controlled self-assembly process that involved adjusting the concentration of dispersed graphene oxide (GO) solutions. Uniform dispersion was achieved using GO coating on the aluminum (Al) surfaces. Graphene encapsulated Al powders (Al/GO) were sintered through spark plasma sintering (SPS) to prepare bulk composites, these were then analyzed to determine the thermal and mechanical properties. The density of the Al/GO composites was determined to be 99% or more compared to the theoretical density of pure Al. The Vicker's hardness and thermal conductivity increased by about 47% and 15% more than the pristine Al bulks. These processes can improve properties of the thermal interface between GO and Al, enabling uniform coating without a crosslinking agent. An Al/GO composite, fabricated through the pH-controlled self-assembly process, should be useful for various applications requiring to high thermal conductivity.
Keywords: ALUMINUM-MATRIX COMPOSITES; MECHANICAL-PROPERTIES; CARBON NANOTUBES; OXIDE